(untitled) (The Review of Diabetic Studies, 2025)
Work pressure, often used interchangeably with job stress, is a multifaceted concept that describes the psychological and physical strain an individual experiences in their professional life. College teachers in India face significant occupational pressure due to a combination of factors, including heavy workloads, administrative burdens, lack of resources, and job insecurity. This pressure often leads to high levels of stress, burnout, and dissatisfaction, negatively impacting both their personal well-being and professional performance. The objective of the study was the various sources of work pressure and its managing strategy among the Arts and science college teachers in Cuddalore of Tamil Nadu. The study based on perception of sample respondents. The purpose of the study, researcher was selected 300 faculties using convenance sampling techniques at different levels were chosen randomly from various departments and functional areas of college keeping in view their total strength and range of activities. It is found that the work pressure of ‘Student Expectations and Parental Involvement’ Economic and Job Security Concerns’ and ‘Administrative and Committee Responsibilities’ in the college are High Levels. The test values indicating the difference in teachers’ perceptions regarding the Strategies to Manage Work are demographic and institution characteristics. work pressure is positive relationship with Strategies to Manage Work pressure in arts and science college in Cuddalore District of Tamil Nadu.